Offshore Distances of Bowhead Whales (Balaena mysticetus) Observed during Fall in the Beaufort Sea, 1982–2000: An Alternative Interpretation - Treacy, Stephen D.; Gleason, Jeffrey S.; Cowles, Cleveland J. (ARCTIC, 2009)
Nineteen years (1982– 2000) of sighting data from fall aerial surveys of bowhead whales (Balaena mysticetus) in the Alaskan Beaufort Sea were analyzed to determine how patterns in the distribution of migrating bowhead whales relate to annual sea-ice conditions. Transect sighting rate (transect sightings/km) indicated (ANOVA; F2, 980 = 143.84, p < 0.0001) that bowhead whales occurred farther offshore in years of heavy ice conditions (73.4 km, 95% CL: 67.2–79.6 km) than in years of moderate (49.3 km, 95% CL: 44.8–53.84 km), or light (31.2 km, 95% CL: 30.0–32.4 km) ice conditions. The most plausible explanation for the observed pattern in bowhead whale distribution is that in years of heavy ice conditions (annual pack ice; 1983, 1988, 1991), the developing landfast ice limits availability of shallow nearshore habitat, thus necessitating use of leads and ice openings in deeper water. We acknowledge that factors such as bathymetry, ocean currents, transport, and food availability may also interact to influence autumn distribution of bowhead whales. In heavy ice years, however, these factors likely exert less influence on bowhead whale distribution than in years with light to moderate ice conditions. Les données automnales prélevées à partir de relevés aériens pendant 19 années chez les baleines boréales (1982– 2000) (Balaena mysticetus) de la mer de Beaufort alaskienne ont été analysées dans le but de déterminer comment les tendances caractérisant la répartition des baleines boréales en migration se rapportent à l’état annuel des glaces et de la mer. Le taux de repérage transect (repérage transect/km) a indiqué (ANOVA; F2, 980 = 143.84, p < 0,0001) que les baleines boréales se trouvaient plus loin au large pendant les années où il y avait beaucoup de glace (73,4 km, 95 % CL: 67,2–79,6 km) que pendant les années où la glace était modérée (49,3 km, 95 % CL: 44,8–53.84 km) ou légère (31,2 km, 95 % CL: 30,0–32,4 km). L’explication la plus plausible à la source de la tendance qui a été observée en matière de ...